Insecticidal and synergistic activity of two monoterpenes against diamondback moth (Lepidoptera: Plutellidae). Issue 2 (2nd January 2018) - Webster, A.E.; Manning, P.; Sproule, J.M.; Faraone, N.; Cutler, G.C.
Abstract: We examined the insecticidal activity of linalool and thymol, against diamondback moth, Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae), and whether they would synergise the activity of spinosad against this pest. Both linalool and thymol were toxic to diamondback moth larvae by topical and oral exposure, but orders of magnitude less so than spinosad. We found that low concentrations of linalool weakly synergised spinosad, increasing its toxicity more than twofold. An interaction between spinosad, and acetone meant it was not possible to identify any potential synergisms between thymol and spinosad. Our results demonstrate limited potential for thymol and linalool to act as biopesticides or synergists for managing diamondback moth.